2001
DOI: 10.1136/jnnp.70.2.174
|View full text |Cite
|
Sign up to set email alerts
|

Controlled randomised crossover trial of the effects of physiotherapy on mobility in chronic multiple sclerosis

Abstract: Objectives-To determine whether physiotherapy can improve mobility in chronic multiple sclerosis and whether there is a diVerence between treatment at home and as a hospital outpatient? Methods-A randomised controlled crossover trial was undertaken in patients with chronic multiple sclerosis who had diYculty walking and were referred from neurology clinics: allocation was to one of six permutations of three 8 week treatment periods separated by 8 week intervals: treatments consisted of physiotherapy at home, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
129
3
6

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(145 citation statements)
references
References 19 publications
7
129
3
6
Order By: Relevance
“…that improvements observed during treatment for MS patients decline over time. Wiles et al 35 reported that treatment benefits lasted only a few weeks after intervention completion and recommended that rehabilitation be continuous or repeated to achieve long-term benefits. The optimal dose of treatment and intervals between treatment episodes are unknown and require continued research.…”
Section: Discussionmentioning
confidence: 99%
“…that improvements observed during treatment for MS patients decline over time. Wiles et al 35 reported that treatment benefits lasted only a few weeks after intervention completion and recommended that rehabilitation be continuous or repeated to achieve long-term benefits. The optimal dose of treatment and intervals between treatment episodes are unknown and require continued research.…”
Section: Discussionmentioning
confidence: 99%
“…23,26 Lord et al com pa red two ne u roph ysio lo gi cal ap pro ac hes; Fa ci li ta ti on ap pro ach and task-ori en ted ap pro ach. 23 Pa ti ents in each gro up sho wed ove rall sig ni fi cant im pro ve ment in ga it out co mes (10 me ter walk test-MWT, stri de length and ri ver me ad vi su al ga it as sess ment-RVGA), howe ver the re was no sig ni fi cant dif fe ren ce bet we en two ne u roph ysi o lo gi cal ap pro ach gro ups.…”
Section: Ne U Roph Ysi O Lo Gi Cal Ap Pro Ac Hesmentioning
confidence: 99%
“…Facilitation approach, Task-oriented approach, Neuromuscular Rehabilitation, Awareness Through Movement, Individual Problem Solving approach) were included in three studies. 23,26,28 Re sis ted exerci ses we re per for med in thre e stu di es. 21,22,24 One study 27 used tre ad mill tra i ning, one study 25 electrot he rapy mo da li ti es and one study 20 pres su re splint app li ca ti on in the ir the rapy pro to cols.…”
Section: In Ter Ven Ti Onsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The GICS has previously been used during clinical trials in gerontology, [4][5][6] psychiatry, 7 chronic pain 8 and multiple sclerosis. 9 It has also been utilised in an SCI research on neuropathic pain and pharmacological therapies. [10][11][12] In addition, we have asked patients to rate their own performance of motor tasks using the GICS.…”
Section: Introductionmentioning
confidence: 99%